2004
DOI: 10.1002/hep.1840400425
|View full text |Cite
|
Sign up to set email alerts
|

Genetic factors influence ethanol-induced uroporphyria in Hfe (—/—) mice

Abstract: Two major risk factors for porphyria cutanea tarda (PCT) are alcohol consumption and homozygosity for the C282Y mutation in the hereditary hemochromatosis gene (HFE). We recently described an animal model for alcohol-induced uroporphyria, using Hfe(-/-) mice. In the present study we show that this effect is dependent on genetic background and ethanol dose. In the 129S6/SvEvTac (129) strain, treatment with 15% ethanol in the drinking water for 6.5 months produced an accumulation of hepatic uroporphyrin (URO) 4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…The finding that the response of mice to EtOH is strain‐specific is consistent with a previous study in which EtOH has been shown to cause uroporphoryria in alcohol‐treated Hfe knockout 129S6/SvEvTac mice but not in Hfe knockout mice with a C57BL/6 background (Gorman et al, 2004). Although in those studies the Hfe knockout in the 129 strain was more sensitive to the effect of alcohol in producing uroporphyria, this effect may not have been mediated by iron, as alcohol is known to induce 5‐aminolevulinic synthase, a rate‐limiting enzyme in porphyrin synthesis.…”
Section: Discussionsupporting
confidence: 91%
“…The finding that the response of mice to EtOH is strain‐specific is consistent with a previous study in which EtOH has been shown to cause uroporphoryria in alcohol‐treated Hfe knockout 129S6/SvEvTac mice but not in Hfe knockout mice with a C57BL/6 background (Gorman et al, 2004). Although in those studies the Hfe knockout in the 129 strain was more sensitive to the effect of alcohol in producing uroporphyria, this effect may not have been mediated by iron, as alcohol is known to induce 5‐aminolevulinic synthase, a rate‐limiting enzyme in porphyrin synthesis.…”
Section: Discussionsupporting
confidence: 91%
“…Effect of Withdrawal from EIP on Hepatic Levels of CYP2E1, CYP3A, and CYP1A2. Alcohol has been shown in rodents to increase hepatic levels of three P450s involved in APAP activation, CYP2E1, CYP3A, and CYP1A2 (Louis et al, 1994;Roberts et al, 1995;Gorman et al, 2004). In all studies investigating alcoholmediated APAP hepatotoxicity, the alcohol-containing liquid diets are withdrawn 11 to 24 h before administration of APAP to ensure complete clearance of alcohol from the blood, because blood ethanol levels as low as 5 mM protect animals from APAP hepatotoxicity (Thummel et al, 1988).…”
Section: Resultsmentioning
confidence: 99%
“…However, we have found that alcohol pretreatment increases APAP hepatotoxicity in Cyp2e1(Ϫ/Ϫ) mice, showing that CYP2E1 is not essential in the alcohol effect (Sinclair et al, 2000c). In other animal studies, alcohol has been reported to also increase CYP3A and CYP1A2 in the liver (Louis et al, 1994;Roberts et al, 1995;Gorman et al, 2004). Human consumption of alcoholic beverages is also associated with increases in CYP3A (Hoshino and Kawasaki, 1995;Niemelä et al, 1998).…”
mentioning
confidence: 85%
“…Some of these may be important in iron homeostasis. The sensitivity of 129S6/SvEvTAC mice to alcohol is greatly increased by the presence of the Hfe -/null gene, causing deposition of iron, but C57BL/6J mice with the same null gene inserted are resistant (161). The sensitivities of inbred strains of mice to uroporphyria induced by iron alone do not correlate with the Ahr genotype, despite the fact that DBA/2 mice remain the most insensitive, whereas an outbred strain gives a range of responses compatible with a variety of genetic factors being involved (145).…”
Section: Genetic Factors In Humansmentioning
confidence: 99%